Geochemical and Mineralogical Characteristics of Garnierite From the Morowali Ni-Laterite Deposit in Sulawesi, Indonesia - Choi, Yuri; Lee, Insung; Moon, Inkyeong (Frontiers in Earth Science, 2021)
The Morowali Ni-laterite deposit is located in the East Sulawesi Ophiolite, which is a large ophiolite belt on Sulawesi Island, Indonesia. The Morowali deposit is developed on a laterite profile due to ophiolite weathering, with saprolite, limonite, and ferruginous cap horizons from the bottom to top. Based on the occurrence of garnierite as the main ore, occurring in the saprolite horizon, it can be said that the ore deposit is a hydrous Mg silicate-type. The Ni ore was classified into different types based on color and XRD and EPMA analyses. Whole-rock geochemical study was also conducted to understand the mineralization process. The Morowali Ni deposit consists of serpentine-like and talc-like phases. The serpentine-like phase consisted of Ni-lizardite and karpinskite (0.76–38.26 wt.% NiO) while the talc-like phase is mainly composed of kerolite (4.02–8.02 wt.% NiO). The serpentine-like garnierite exhibits high Ni and Fe contents and occurrence similar to that of the serpentine observed in the saprolite horizon, suggesting the serpentine-like garnierite originated from the bedrock, and Mg-Ni cation exchange occurred during laterization. Contrastingly, the lower Fe content of the talc-like phase (0.01–0.05 wt.%) compared to the serpentine-like phase (0.14–7.03 wt.%) indicates that the talc-like garnierite is of secondary origin since Fe is immobile during weathering. The Morowali Ni-laterite deposit was mainly formed during laterization; however, the repeated dry and wet cycles in each year results in the formation of secondary garnierite.